The (un)constitutionality of the financial investigation as provided by the Financial Administration Act – a case study - Flander, Benjamin (Varstvoslovje, 2022)
Purpose: The article provides an in-depth analysis of the regulation of financial investigations under the Financial Administration Act (“Zakon o finančni upravi (ZFU)”, 2014) and the manner of implementing the regulatory framework of this instrument in Slovenia. It presents the conditions for the initiation of a financial investigation, along with the competence and authorisations of investigators, the status of a person under investigation, and the procedure and conclusion of a financial investigation. In the article we take the position that either the existing regulatory framework or the manner in which the regulatory framework of financial investigation is implemented is unconstitutional. Design/Methods/Approach: We applied the normative method, the analysis and synthesis method, and a case study. Findings: We claim that Article 100 of the “ZFU” (2014), which governs financial investigations, is not compliant with the Constitution or the manner in which this provision is implemented by the Financial Administration of the Republic of Slovenia, which also has support in courts’ decisions. The Financial Administration, the Administrative Court and courts of general jurisdiction interpret and implement Article 100 of the “ZFU”, in the section relating to the moment in which a financial investigation is completed and tax inspection proceedings begin, in a way that is not compliant with the explanation by the Constitutional Court of the Republic of Slovenia in decision No. U-I-69/22-4. Research Limitations/Implications: The research does not include a comparative analysis, i.e., an analysis of the regulation and practice of conducting financial investigations pertaining to infringements of tax regulations in other countries.
Keywords: constitution; financial administration; Financial Administration Act; financial investigations; finančna uprava; finančne preiskave; ustava; Zakon o finančni upravi